Studi Takhrij dan Syarah Hadis tentang Dampak Praktik Riba dalam Kehidupan Ekonomi - Lina Sapariah; Shifwah Salsabila Zahira; Dadah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about usury. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about usury in Muslim history No. 2995. The results and discussion of this study indicate that the quality of the hadith regarding usury is considered authentic with the qualifications of maqbul ma'mul bih for the Islamic experience in avoiding usury which has a detrimental impact on society. This study concludes that the hadith narrated by Muslim No. 2995 is relevant to be used as the basis for the development of the Islamic economy to create community welfare in Indonesia.